PP09 Assessing the Potential Effect of Healthy Eating Policy Interventions on Socioeconomic Inequalities: Systematic Review. (10th September 2013) - R, McGill; Anwar, E; Orton, L; Taylor-Robinson, D C; Bromley, H; Lloyd-Williams, F; Calder, N; O'Flaherty, M; Castillo, M Guzman; White, M; Petticrew, M; White, M M; et al.
Abstract : Background: Cardiovascular disease (CVD) is one of the main contributors to health inequalities. CVD primary prevention includes potentially powerful interventions to promote healthy eating. However, might some dietary interventions actually widen the heath gap between rich and poor, thus leading to intervention-generated inequalities? Objective: To systematically review the evidence for differential socio-economic effects associated with healthy eating policy interventions. Methods: We initially searched two bibliographic databases (MEDLINE & Psycinfo) using a piloted search strategy. Results from further databases and additional sources will be reported in the final review. Search results were screened independently by two reviewers. We included evaluations of policy interventions to promote healthier diets, (defined as the reduced intake of salt, sugar, trans fats, saturated fat, total fat, or total calories, or increased consumption of fruit and vegetables). All quantitative studies were eligible for inclusion. Studies were only included if quantitative results were presented by socio-economic group (SEG), defined by income, education level, ethnicity, or occupational status. Extracted data were categorised with a modified version of the 4Ps marketing framework: Price, Product, Place and Promotion, with a 5 th "P" labelled "Personal", relating to person-based health education. Based on preliminary findings included studies were synthesised as a narrative review due to their heterogeneous nature. Results: We identified 14, 449 studies in the initial search and reviewed 47 full text papers. Following screening, only 14 articles met the inclusion criteria. Preliminary results analysed using the "5 P's" framework suggest that some food policy interventions may generate socio-economic differentials. Price interventions showed the greatest potential to reduce health inequalities (3 of 5 studies). Conversely, Personal interventions tended to widen inequalities (3 of 4 studies showed preferential outcomes in higher SEGs). Results relating to Place interventions were mixed, with 2 school-based studies reporting a preferential outcome in higher SEGs, and 1 work-based study reporting a preferential outcome in lower SEGs. Evidence for Product and Promotion interventions appears sparse, with only 1 study found for each category. However, both reporting preferential outcomes in higher SEGs. Conclusion: Interventions categorised by the "5 P's" show differential effects on healthy eating outcomes by SEG, with interventions categorised as Personal appearing the most likely to increase health inequalities. However the vast majority of studies retrieved did not explore differential effects by socio-economic group. Future policies aimed at improving population health should be routinely evaluated for their potential impact on health inequalities.